ANALYSIS OF ASSET GROWTH, CAPITAL STRUCTURE AND COMPANY PROFITABILITY (CASE STUDY OF PT FAJAR GRAHA PENA MAKASSAR) - Mukminati, Mukminati (Jurnal Ekonomi Balance, 2018)
PT. Fajar Graha Pena Makasssar is one of the biggest media company in South Sulawesi which starts from media print business called Fajar Newspapers. Many years ago, the company have fluctuation financial experience. But after the CEO decided to make join cooperation with Kalla Group and Jawa Pos, the company remains bigger. Many companies and Non-govermental organization wants to made join cooperation or put their investation and indeed change the bussines model, related to the asset growth, capital structure, and PT. Fajar Graha Pena profitability. The research  that has been done, by interviewing and collecting Financial report data analytical. The analysis was used by calculating related ratio with the asset growth, capital structure ratio, and profitability ratio.  Research result shows the three of the ratio had fluctuating, the asset growth”s been very good, while the capital structure and the company profitability still needs to be improved.